Habitat assessment, population characteristics, and conservation recommendations for Nepali paper plant, Daphne bholua: ensuring the future of handmade paper production in Nepal’s Central Himalayas - Bikram Jnawali; James Ojascastro; Ajay Neupane; Shristhi Nepal; Robbie Hart; Suresh Kumar Ghimire (Environmental Research Communications)
Daphne bholua Buch. -Ham. ex D. Don (Thymelaeaceae) is a woody shrub native to the temperate forests of the Himalaya. Since the 12th century, the bark of D. bholua has been used as a raw material for handmade paper in Nepal, and employed for value-added products, including government documents, and religious texts. However, unsustainable commercial harvesting now threatens this centuries-old artisanal tradition. To inform and improve the conservation of this important species, we evaluated its habitat characteristics, size class distribution, and regeneration status along an elevation gradient (1900–2500 m) in Madane Mountain, central Nepal. We established 108 plots (5 m× 5 m) at three sites, each with three canopy types: closed, semi-closed, and open. We analyzed habitat characteristics, considering variations in physical and topographic variables and patterns of associated species in different elevation sites. D. bholua exhibited the highest mean density at higher elevations with minimal disturbance, whereas the lowest elevation site, experienced greater human disturbance, with the lowest density. Furthermore, the population structure displayed a ‘reverse J-shaped’ curve, suggesting favorable conditions for natural recruitment and regeneration. Our research findings also indicate that D. bholua populations thrive in semi-closed forest canopies, particularly when associated with Rhododendron arboreum , Quercus semecarpifolia , and Sarcococca coriacea. The outcomes may hold significant value for policymakers, conservationists, harvesters, paper manufacturers, and regulatory bodies aiding in development of environmentally sound conservation programs tailored to various elevations. Our key recommendation may appear surprising: we advise establishing a small, meticulously managed hand papermaking industry in the villages linked to Madane and nearby areas. This initiative would generate supplemental income and produce a culturally valuable and economically marketable product.